Balticeler kerneggeri gen. nov., sp. nov., an enigmatic Baltic amber fossil of the ground beetle subfamily Trechinae (Coleoptera, Carabidae) - Joachim Schmidt; Stephan Scholz; David R. Maddison (Deutsche Entomologische Zeitschrift, 2021)
Balticeler kerneggeri gen. nov., sp. nov., is described based on six fossil specimens preserved in Eocene Baltic amber and imaged using light microscopy and X-ray micro-computed tomography. Based on certain characters observed in the fossil species it is considered a “middle grade” Carabidae, outside of the large family Harpalinae (as it possesses a scrobal seta, the lack of which is a synapomorphy of that subfamily), but possessing four synapomorphies that indicate Balticeler belongs to a large clade of carabids including Harpalinae (anisochaetous Grade B antennal cleaner, conjunct mesocoxae, closed procoxal cavities, and a well-developed external lobe of the metepimeron). This remarkable beetle has several striking features, including lack of externally-visible sexually dimorphic characters, lack of lateral borders on the pronotum, and very long and thin mandibles and maxillae. In combination, these states are unique within Carabidae. We consider the presence of a dorsally completely open aedeagal median lobe as a synapomorphy of the fossil species with the subfamily Trechinae, a pubescent and relatively long second antennomere and a 4+2+2 pattern of umbilicate setae as synapomorphies of the supertribe Trechitae, and a quadrisetose clypeus as a synapomorphy with the Trechitae clade Bembidarenini + Trechini sensu Maddison et al. (2019). As it lacks a synapomorphy of Bembidarenini + Trechini, we propose that it is a member of the stem group of that clade.